An Overview of Waste Materials for Sustainable Road Construction - Yuriz, Yasmin; Tuan Ismail, Tuan Noor Hasanah; Mat Hassan, Nik Normunira (International Journal of Sustainable Construction Engineering and Technology, 2020)
Untreated soil typically has low shear strength, swelling behavior, high compressibility and its characteristics were highly dependent on the environment. In general, such problematic soil will lead to severe damages in road construction industry such as bearing capacity failure, slope instability, and excessive settlement. Agricultural waste, construction waste, and municipal waste have recently gained considerable attention as a sustainable material in road construction application due to its availability, environmental friendly and low-cost materials. Therefore in this review, randomly distributed fiber reinforced soil and oriented distributed fiber reinforced soil will be extensively discussed based on the emerging trend. It further reviewed the feasibility of using waste materials as a reinforcement material for the road construction industry. The review also attempts to evaluate and compare the engineering properties of soil and sustainable materials in order to enhance soil performance as well as help to improve the environment affected by growing waste materials.